Cytochrome c‐Capped Fluorescent Gold Nanoclusters: Imaging of Live Cells and Delivery of Cytochrome c. Issue 13 (6th April 2016) - Chattoraj, Shyamtanu; Amin, Md. Asif; Bhattacharyya, Kankan
Abstract: Cytochrome  c ‐capped fluorescent gold nanoclusters (Au‐NCs) are used for imaging of live lung and breast cells. Delivery of cytochrome  c inside the cells is confirmed by covalently attaching a fluorophore (Alexa Fluor 594) to cytochrome  c ‐capped Au‐NCs and observing fluorescence from Alexa 594 inside the cell. Mass spectrometry studies suggest that in bulk water, addition of glutathione (GSH) to cytochrome  c ‐capped Au‐NCs results in the formation of glutathione‐capped Au‐NCs and free apo‐cytochrome  c . Thus glutathione displaces cytochrome  c as a capping agent. Using confocal microscopy, the emission spectra and decay of Au‐NCs are measured in live cells. From the position of the emission maximum it is shown that the Au‐NCs exist as Au8 in bulk water and as Au13 inside the cells. Fluorescence resonance energy transfer from cytochrome  c –Au‐NC (donor) to Mitotracker Orange (acceptor) indicates that the Au‐NCs localise in the mitochondria of live cells. Abstract : Please remove your cap ! In this study, mitochondrial imaging of live cells, using Au nanoclusters (Au‐NCs) capped by cytochrome  c that is labeled with Alexa Fluor 594, involves FRET from the Au‐NCs to the Alexa dye. The cytochrome  c ‐capped Au‐NCs localize in the mitochondria of a live cell, where it interacts with glutathione leading to release of the cytochrome  c inside the cell, thus switching off the FRET signal.